MICROBIAL RESPIRATION AND DIFFUSIVE TRANSPORT OF O2, 16O2, AND 18O16O IN UNSATURATED SOILS: A MESOCOSM EXPERIMENT - Hendry M.J.; Wassenaar L.I.; Birkham T.K. (My University, 2002)
Although the flux of molecular O2 between the atmosphere and the subsurface is intrinsically linked to the net soil production of greenhouse gasses, few studies have focused on the controls affecting the isotopic composition of O2 in the subsurface. Here, we developed and tested a stable oxygen isotope tracer technique and gas transport modeling approach to evaluate O2 cycling and fluxes from the subsurface that used an environmentally controlled soil mescosm. We measured the O2 and δ18O2 profiles in a model unsaturated soil zone and quantified the O2 consumption rates and the O2 isotope fractionation factors resulting from the combined processes of subsurface microbial (including bacteria, fungi, and protozoa) consumption of O2 and diffusive influx of O2 from the atmosphere. We found that at high respiration rates in the mesocosm, there appeared to be very little isotope fractionation of O2 by soil microorganisms. Although the mesocosm respiration rates are not typical of natural soils in northern temperate climes, they may be more representative of soils in warm and moist tropical environments. Our findings caution against the indiscriminate application of laboratory-determined oxygen isotope fractionation factors to field settings. The oxygen isotope tracer and modeling approach demonstrated here may be applied to gain a better understanding of biogenic gas production and O2 cycling in subsurface systems and soils.